Policy optimization in providing green open spaces by urban government: A comparative study in streetscape design approaches - Merinda, Herlina; Mahanani, Yekti Mei (Journal of Placemaking and Streetscape Design, 2025)
Background: Green Open Space (GOS) in urban areas is experiencing a significant decline in quality and quantity due to rapid population growth and urbanization. This growth drives land conversion for urban infrastructure, including buildings, trade, industry, and residential areas. In Indonesia, the provision of GOS is mandated by Law Number 11 of 2020, which stipulates that urban areas must allocate 30% of their land for GOS (20% public and 10% private). Methods: This study employs both qualitative and quantitative methods. The qualitative method explores geographic and societal conditions, as well as policies, success stories, and challenges in providing Green Open Space (GOS) in Jakarta, Surabaya, and Samarinda. This involves a literature review of statistical data, prior research, and policy documents, as well as secondary data to analyze GOS conditions and needs based on regulations. Challenges in fulfilling GOS are categorized into technical, policy, and political aspects. The quantitative method uses the Analytic Hierarchy Process (AHP) to prioritize policies for achieving the 30% GOS target in the three cities. Findings: The study identified five key priorities for GOS policy implementation based on AHP calculations: Commitment of leaders and political actors, Stakeholder collaboration, Availability of green regulations, Community participation, and Private sector involvement. The research highlighted that cities with lower population densities, such as Samarinda, have a comparative advantage in achieving the 30% GOS target compared to denser cities like Jakarta and Surabaya. Furthermore, the study emphasized the role of heterogeneous community characteristics in shaping the effectiveness of GOS policies. Achieving sustainable urban development requires a strong commitment from policymakers and local communities. Novelty/Originality of This Article: This research provides a novel perspective on GOS policy optimization by integrating AHP analysis with urban land-use strategies. This research highlights the importance of contextual factors, such as population density and community heterogeneity, in successfully implementing GOS policies.